Investigation of a Random-Fractal Antenna Based on a Natural Tree-Leaf Geometry - Hatem Rmili; Donia Oueslati; Imen Ben Trad; Jean Marie Floch; Abdullah Dobaie; Raj Mittra (International Journal of Antennas and Propagation)
In this paper, we investigate a new printed antenna based on the 2D image of a fractal tree-leaf geometry by studying the effect of the irregular boundary of the proposed antenna on its radiation characteristics. Both the impedance matching properties and the radiation patterns of the antenna are studied over the frequency band 1–6 GHz. Four configurations are designed by increasing the complexity of the structure, which ranges from iteration 0 to iteration 3. The fractal properties of the proposed tree-leaf antenna are then compared to those of a conventional fractal antenna with smooth edges. Following this, the proposed antennas are fabricated and characterized experimentally. Finally, results are analyzed and discussed, and a practical application for this new type of antennas is proposed.